High Throughput Approaches to Unravel the Mechanism of Action of a New Vanadium-Based Compound against Trypanosoma cruzi - M. Florencia Mosquillo; Pablo Smircich; Analía Lima; Sergio A. Gehrke; Gonzalo Scalese; Ignacio Machado; Dinorah Gambino; Beatriz Garat; Leticia Pérez-Díaz (Bioinorganic Chemistry and Applications)
Treatment for Chagas disease, a parasitosis caused by Trypanosoma cruzi, has always been based on two drugs, nifurtimox and benznidazole, despite the toxic side effects described after prolonged prescription. In this work, we study a new prospective antitrypanosomal drug based on vanadium, here named VIVO(5Brsal)(aminophen). We found a good IC50 value, (3.76 ± 0.08) μM, on CL Brener epimastigotes. The analysis of cell death mechanism allowed us to rule out the implication of a mechanism based on early apoptosis or necrosis. Recovery assays revealed a trypanostatic effect, accompanied by cell shape and motility alterations. An uptake mostly associated with the insoluble fraction of the parasites was deduced through vanadium determinations. Concordantly, no drastic changes of the parasite transcriptome were detected after 6 h of treatment. Instead, proteomic analysis uncovered the modulation of proteins involved in different processes such as energy and redox metabolism, transport systems, detoxifying pathways, ribosomal protein synthesis, and proteasome protein degradation. Overall, the results here presented lead us to propose that VIVO(5Brsal)(aminophen) exerts a trypanostatic effect on T. cruzi affecting parasite insoluble proteins.